Ritual Practice and Exchange in the Late Prehispanic Western Pueblo Region: Insights from the Distribution and Deposition of Turquoise at Homol'ovi I†. Issue 3 (2nd July 2016) - Hedquist, Saul L.
Abstract : Archaeological and ethnographic evidence demonstrate the importance of turquoise among past and present Pueblo groups. In this paper, I examine the social uses of turquoise and other blue-green minerals at Homol'ovi I, a late prehispanic Hopi village and the most intensively excavated site within the Homol'ovi Settlement Cluster. I explore intrasite patterns of deposition (i.e., the content and context of turquoise deposits) and stylistic variation among objects in an effort to identify differential practices and material expressions within the pueblo. In addition, I assess the geologic provenance of turquoise from the site using high-precision measurements of lead and strontium isotopes. Recent studies indicate turquoise from at least two geologic locales—the Cerrillos Hills (New Mexico) and Canyon Creek (Arizona)—was acquired by Homol'ovi I inhabitants. These source investigations, coupled with those from other contemporaneous sites in the region, clarify the flow of turquoise across the late prehispanic Western Pueblo landscape and illuminate regional patterns of acquisition and exchange.